Improving the Critical Thinking Skills of Elementary School Students through Problem Based Learning and Inquiry Models in Social Science Learning - Haryanti, Yuyun Dwi; Sapriya, Sapriya; Permana, Johar; Syaodih, Erna Wulan; Kurino, Yeni Dwi (UIN Siber Syekh Nurjati Cirebon, 2022)
AbstractThe critical thinking skills are an important component to be instilled in elementary schools. The purpose of this study was to test the critical thinking skills of fifth grade students elementary school through the Problem Based Learning model and the Inquiry model based on the interest in learning social science using authentic assessments. Employing a quasi-experiment with Pretest-Posttest Control Group Design, this study involved 49 fifth grade elementary school students in two classes. A total of 24 students in the experimental class A learned using the Problem Based Learning (PBL) model, whereas 25 students in the experimental class B learned using the Inquiry model. The data were collected using description tests and questionnaires. The test was based on the level of reliability of 0.551, while the questionnaire with reliability of 0.893 was tested using ANOVA. The results of the study revealed that the implementation of the PBL model in social science learning was quite effective in improving critical thinking skills compared to the Inquiry model. The highest critical thinking ability was in students who had high learning interest in social science learning. This research contributed differently to the improvement of the social science learning process to acquire one of the 21st century thinking skills.Keywords: problem-based learning model, inquiry model, critical thinking.Abstrak Kemampuan berpikir kritis merupakan komponen penting yang perlu ditanamkan di sekolah dasar. Tujuan penelitian ini adalah untuk menguji kemampuan berpikir kritis siswa kelas V sekolah dasar melalui model Problem Based Learning (PBL) dan model Inquiry berdasarkan minat belajar mata pelajaran IPS dengan menggunakan penilaian autentik. Menggunakan eksperimen semu dengan Pretest-Posttest Control Group Design, penelitian ini melibatkan 49 siswa kelas V sekolah dasar. Sebanyak 24 siswa di kelas eksperimen A belajar dengan model Problem Based Learning, sedangkan 25 siswa pada kelas eksperimen B belajar dengan model Inquiry. Data dikumpulkan dengan menggunakan tes deskripsi dan kuesioner. Pengujian didasarkan pada tingkat reliabilitas 0,551, sedangkan kuesioner dengan reliabilitas 0,893 diuji menggunakan ANOVA. Hasil penelitian menunjukkan bahwa penerapan model PBL dalam pembelajaran IPS cukup efektif dalam meningkatkan kemampuan berpikir kritis dibandingkan dengan model Inquiry. Kemampuan berpikir kritis tertinggi terdapat pada siswa yang memiliki minat belajar yang tinggi pada pembelajaran IPS. Penelitian ini memberikan kontribusi yang berbeda terhadap peningkatan proses pembelajaran IPS untuk memperoleh salah satu keterampilan berpikir abad 21.Kata kunci: model PBL, model inquiry, berpikir kritis.